Tobacco use among school students in Manipur, North East India: a cross-sectional study - Laishram, Jalina; Rafique, Mohammed; Singh, Kh. Sonarjit; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2020)
Background: Tobacco use is one of the most common substance abuse indulged by adolescents worldwide. The current tobacco use among youths in the age group of 13-15 years was 14.6% (GYTS 2009, India). The tobacco situation in India is unique because of a vast spectrum of tobacco products available for smoking as well as smokeless use. This study was done to determine the prevalence of tobacco use among school students in Imphal, Manipur, India and to determine the association between tobacco use and socio-demographic characteristics. Methods: A cross sectional study was conducted among school students studying in class VII to class X in Imphal, Manipur using convenience sampling. Data were collected by questionnaire method. Descriptive statistics like mean, percentages and proportions were used. Chi-square test was used to determine the association and a p value of <0.05 was taken as significant. Results: The prevalence of ever use of tobacco among school students in Imphal was found to be 19.5%. And 43.4% of the ever users were current users. Ever use of tobacco was significantly associated with older age group (14-17 years), male gender, living in a nuclear family, studying in class X, being in a relationship and whose mother was educated below class X. Conclusions: Two out of every 10 students in the age group of 10-17 years in the study have ever used any kind of tobacco product. Smokeless form of tobacco was more commonly used as compared to smoked form.